The Third Italian Consensus Conference for Malignant Pleural Mesothelioma: State of the art and recommendations. (August 2016) - Novello, S.; Pinto, C.; Torri, V.; Porcu, L.; Di Maio, M.; Tiseo, M.; Ceresoli, G.; Magnani, C.; Silvestri, S.; Veltri, A.; Papotti, M.; Rossi, G.; et al.
Abstract: Malignant Pleural Mesothelioma (MPM) remains a relevant public health issue, and asbestos exposure is the most relevant risk factor. The incidence has considerably and constantly increased over the past two decades in the industrialized countries and is expected to peak in 2020–2025. In Italy, a standardized-rate incidence in 2011 among men was 3.5 and 1.25 per 100, 000 in men and women, respectively, and wide differences are noted among different geographic areas. The disease remains challenging in terms of diagnosis, staging and treatment and an optimal strategy has not yet been clearly defined. The Third Italian Multidisciplinary Consensus Conference on Malignant Pleural Mesothelioma was held in Bari (Italy) in January 30–31, 2015. This Consensus has provided updated recommendations on the MPM management for health institutions, clinicians and patients.